Rôle des habitants dans l’invention de nouvelles formes d’urbanité dans la périphérie de Constantine (Algérie). Le cas de la ville nouvelle Ali Mendjeli - Ahcène Lakehal (L’Année du Maghreb)
This article explores the role of ordinary citizens in the regionalization processes that have been affecting the New Town of Ali Mendjeli for over 15 years. More specifically, we have attempted - while providing factual information on a little known New Town which, today, is undoubtedly one of the main stages for territorial dynamics in Algerian peripheries - to understand how people / users, through the skills they mobilize in their practices and through the play of their representations, take over from the government the “reshaping” of the New Town in territorializing its spaces, shaping the landscape and giving substance to its body and urbanity. As a background to the analysis of the role of the inhabitants’ initiatives in the creation of the New Town, this study also tries to highlight the changes that affect the lifestyles of people and their ways of living, their presence in town and their perception of the City.